2007
DOI: 10.1291/hypres.30.395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Olmesartan on Oxidative Stress in Hemodialysis Patients

Abstract: The effect of olmesartan, an inverse angiotensin II type 1 receptor blocker (ARB), on oxidative stress in hemodialysis (HD) patients is not fully understood, and has not been widely investigated in vitro or in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
(46 reference statements)
0
30
0
Order By: Relevance
“…[16][17][18][19] We previously reported that olmesartan exhibited antioxidant activity in HD patients, even though it was used as a clinical dose for the first time. 6) From the findings of this clinical study, it is also possible that the antioxidant properties of olmesartan are independent of its antihypertensive activity. Therefore, we examined the issue of whether or not the antioxidant properties of olmesartan are related to its phar- macological activity, such as blood lowering effect and renoprotective action using CRF model rats.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…[16][17][18][19] We previously reported that olmesartan exhibited antioxidant activity in HD patients, even though it was used as a clinical dose for the first time. 6) From the findings of this clinical study, it is also possible that the antioxidant properties of olmesartan are independent of its antihypertensive activity. Therefore, we examined the issue of whether or not the antioxidant properties of olmesartan are related to its phar- macological activity, such as blood lowering effect and renoprotective action using CRF model rats.…”
Section: Discussionmentioning
confidence: 86%
“…These phenomena were very similar to the results obtained from a clinical study involving HD patients. 6) For example, in both CRF rats and HD patients, the oxidized albumin ratio was significantly decreased at 4 weeks by the administration of olmesartan (Fig. 2).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…[16][17][18] Serum samples were immediately frozen and stored at Ϫ80°C until used for analysis. From the HPLC profile, the content of each albumin fraction (rat mercaptalbumin, f[RMA]; rat nonmercaptalbumin, f[RNA]) was estimated as the area of the RNA fraction divided by the RMA fraction of the serum albumin peak.…”
Section: Methodsmentioning
confidence: 99%